2001
DOI: 10.2166/wst.2001.0220
|View full text |Cite
|
Sign up to set email alerts
|

Influence of porosity and composition of supports on the methanogenic biofilm characteristics developed in a fixed bed anaerobic reactor

Abstract: This paper reports on the influence of the material porosity on the anaerobic biomass adhesion on four different inert matrices: polyurethane foam, PVC, refractory brick and special ceramic. The biofilm development was performed in a fixed-bed anaerobic reactor containing all the support materials and fed with a synthetic wastewater containing protein, lipids and carbohydrates. The data obtained from microscopic analysis and kinetic assays indicated that the material porosity has a crucial importance in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
7

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 0 publications
3
24
0
7
Order By: Relevance
“…Their corresponding removal values reached, 76.7, 77 and 86.2%, respectively, with corresponding residual values of 85, 54 and 28 mg/l. These results indicated that the use of the packing material (lamella sheets) enhanced the removal effi ciency of the organic materials [8]. These results are in agreement with Refs.…”
Section: Effect Of Hrt (6 H)supporting
confidence: 92%
See 1 more Smart Citation
“…Their corresponding removal values reached, 76.7, 77 and 86.2%, respectively, with corresponding residual values of 85, 54 and 28 mg/l. These results indicated that the use of the packing material (lamella sheets) enhanced the removal effi ciency of the organic materials [8]. These results are in agreement with Refs.…”
Section: Effect Of Hrt (6 H)supporting
confidence: 92%
“…Specifi c surface area, porosity, surface roughness, pore size and orientation of the packing material was found to play an important role in anaerobic reactor performance. Many carrier materials have been investigated regarding their suitability as supports for bio-fi lm, including cheap, readily available material like sand, clay, glass, quartz and a number of plastics [8]. In nature, microorganisms inhabit the outer and inner surfaces of stones, gravel or sand.…”
Section: Introductionmentioning
confidence: 99%
“…The general growth [24] and the microbial community [25] of biofilm on carriers are depending on physicochemical surface properties of the carriers.…”
Section: Biofilm Formationmentioning
confidence: 99%
“…Many carrier materials have been investigated regarding their stability as support for biofilm, including cheap, readily available materials like, sand, clay, glass, quartz and a number of plastics [8]. Picanco et al [9] reported that the efficiency of removing organic matters in fixed-bed reactors is directly related to the characteristics of the support material used for immobilization of anaerobes. It is widely accepted that organic support material has a higher affinity than inorganic material [10].…”
Section: Introductionmentioning
confidence: 99%